(untitled) (Journal of Social Sciences Review, 2024)
The present study carried out to identify the students’ personality type at university of Swabi. Objectives of the study were to explore the students’ personality types at university of Swabi and to examine the more frequent type of students’ personality. All undergraduate students studying in the colleges of Education affiliated with University of Swabi constituted the population of the study. Out of total population, 5 students were selected through random sampling technique. To collect data from the respondents, a closed ended questionnaire MBTI containing 70 items based on 2 points scale with the consultation of the supervisor in relation to the objective of the subject. Findings of the study concluded that half of the respondents were extrovert and half of the respondents were introvert. Majority of the respondents were intuitive associated with intuitive and sensing type. Half of the subjects were thinking type and other half were feeling type personality. Greater number of participants having perceiving personality type. It was recommended that the similar study might be replicated at elementary level. The study might be replicated on exploring personality type in other departments of university of Swabi.